Źli chrześcijanie w Kościele w świetle nauczania św. Augustyna - Terka, Mariusz (Vox Patrum, 2013)
The main perspective from which St. Augustine describes the Church, is the category of good and evil. It is included in the image of the heavenly Jerusalem understood as a community of saints in heaven, Zion as a symbol of the pilgrim Church and the metaphor of Babylon, which is the kingdom of evil and persecutor of the followers of Christ. The Church on earth exists between Jerusalem and Babylon, and for this reason there are both good and bad people. That confusion is an important feature of Augustine’s Church in its earthly dimension. Saints Christians are trying to improve the bad members of the Body of Christ, but they are also forced to tolerate the evil that they cannot change, and bad Christians can persecute the good ones. Augustine calls their mutual relationship the spiritual battle. The judgment of them, and their final separation belongs to God only, and it will be done during the Final Judgement.